Average Error: 0.1 → 0
Time: 4.7s
Precision: 64
\[e^{x + 1} - e^{x + 1}\]
\[0\]
e^{x + 1} - e^{x + 1}
0
double f(double x) {
        double r45590025 = x;
        double r45590026 = 1.0;
        double r45590027 = r45590025 + r45590026;
        double r45590028 = exp(r45590027);
        double r45590029 = r45590028 - r45590028;
        return r45590029;
}

double f(double __attribute__((unused)) x) {
        double r45590030 = 0.0;
        return r45590030;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.1

    \[e^{x + 1} - e^{x + 1}\]
  2. Simplified0

    \[\leadsto \color{blue}{0}\]
  3. Final simplification0

    \[\leadsto 0\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "exp(x+1)-exp(x+1)"
  (- (exp (+ x 1.0)) (exp (+ x 1.0))))